2022
DOI: 10.1101/2022.05.25.493495
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Oral cholestyramine prevents enrichment of diverse daptomycin-resistance mutations in intestinal Enterococcus faecium

Abstract: Background and ObjectivesPreviously, we showed proof-of-concept in a mouse model that oral administration of cholestyramine prevented enrichment of daptomycin-resistant Enterococcus faecium in the gastrointestinal (GI) tract during daptomycin therapy. Cholestyramine binds daptomycin in the gut, which removes daptomycin selection pressure and so prevents the enrichment of resistant clones. Here, we investigated two open questions related to this approach: 1) can cholestyramine prevent the enrichment of diverse … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1
1

Relationship

2
0

Authors

Journals

citations
Cited by 2 publications
(8 citation statements)
references
References 30 publications
0
8
0
Order By: Relevance
“…We previously demonstrated that the oral administration of cholestyramine IXB concurrent with systemic DAP treatment very substantially prevented the up selection and shedding of DAP resistant VREfm. 8,9 In this study, we The DAP removal efficacy of IXB in the FaSSIF was slightly higher than in the FeSSIF as a result of lower bile acid concentration. This work lays the foundations for optimizing the use of ion exchange sorbents, such as cholestyramine, as adjuvant therapy to prevent daptomycin resistance, as well as designing next generation biomaterials that could combat the emergence of antimicrobial resistance in the GI tract.…”
Section: Discussionmentioning
confidence: 66%
See 3 more Smart Citations
“…We previously demonstrated that the oral administration of cholestyramine IXB concurrent with systemic DAP treatment very substantially prevented the up selection and shedding of DAP resistant VREfm. 8,9 In this study, we The DAP removal efficacy of IXB in the FaSSIF was slightly higher than in the FeSSIF as a result of lower bile acid concentration. This work lays the foundations for optimizing the use of ion exchange sorbents, such as cholestyramine, as adjuvant therapy to prevent daptomycin resistance, as well as designing next generation biomaterials that could combat the emergence of antimicrobial resistance in the GI tract.…”
Section: Discussionmentioning
confidence: 66%
“…We previously demonstrated that the oral administration of cholestyramine IXB concurrent with systemic DAP treatment very substantially prevented the up selection and shedding of DAP resistant VRE fm . 8, 9 In this study, we shed light on the mechanism and engineering aspects of IXB-mediated DAP removal. DAP tends to self-assemble into micelles or aggregates in aqueous solutions and re-assemble to form SLBs upon contacting the IXB, which triggers the time-dependent molecular diffusion of DAP inside the IXB pores.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…This is consistent with off-target selection for resistance, where antibiotic use causes resistance evolution in a population of bacteria that are not the therapeutic target. Direct experimental evidence of off-target selection comes from mouse models: systemic DAP treatments enriched DAP-resistant VRE fm in the GI tract and up-selected a variety of de novo resistance mutations that confer DAP resistance. , This raises the prospect that inactivation of DAP in the GI tract would prevent the evolution of DAP resistance without interfering with the capacity of DAP to treat bloodstream infections. This would reduce the risk that patients would acquire DAP-resistant VRE fm from their carriage populations in their own GI tract, as well as prevent the onward transmission of DAP resistance in this important hospital-acquired infection.…”
Section: Introductionmentioning
confidence: 99%